Hunger & satiety signals: another key mechanism involved in the NAFLD pathway - López-Méndez, Iván; Maldonado-Rojas, Andrea Del Carmen; Uribe, Misael; Juárez-Hernández, Eva (Frontiers in Endocrinology, 2023)
Non-alcoholic fatty liver disease (NAFLD) is a highly prevalent metabolic disease, although prevalence could change according to region, nowadays is considered a public health problem whose real impact on the health system is unknown. NAFLD has a multifactorial and complex pathophysiology, due to this, developing a unique and effective pharmacological treatment has not been successful in reverting or avoiding the progression of this liver disease. Even though NAFLD pathophysiology is known, all actual treatments are focused on modifying or regulating the metabolic pathways, some of which interplay with obesity. It has been known that impairments in hunger and satiety signals are associated with obesity, however, abnormalities in these signals in patients with NAFLD and obesity are not fully elucidated. To describe these mechanisms opens an additional option as a therapeutic target sharing metabolic pathways with NAFLD, therefore, this review aims to describe the hormones and peptides implicated in both hunger-satiety in NAFLD. It has been established that NAFLD pharmacological treatment cannot be focused on a single purpose; hence, identifying interplays that lead to adding or modifying current treatment options could also have an impact on another related outcome such as hunger or satiety signals.